Research on the Overall Design and Water Entry Simulation of Cross-Media Unmanned Underwater Vehicles - Wenye Li; Wuwei Wu; Quanming Miao; Jiahu Wu (Journal of Marine Science and Engineering)
Novel cross-media vehicles can operate efficiently in different media where water entry is a critical process. In this paper, a water–air cross-media unmanned vehicle is designed and its hydrodynamic characteristics during water entry are studied. With the use of STARCCM, the movement of the vehicle during water entry was simulated with the adoption of a VOF multiphase flow model and a Schnerr–Sauer cavitation model and its accuracy was tested. The flow field characteristics of the vehicle under common operating conditions, as well as the influence of the initial water entry speed and angle on the motion state and the force endured by the vehicle under different operating conditions, were simulated. The results show that the overall operating attitude of the vehicle is stable, and the influence of the water entry speed is more significant than that of the water entry angle. The research results provide a theoretical basis and technical support for the design and application of cross-media vehicles, helping to promote cross-media navigation technology.